2017
DOI: 10.1038/s41598-017-00075-1
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Association Studies of Anthracycline-induced Cardiotoxicity: A Systematic Review and Meta-analysis

Abstract: Anthracyclines play an important role in the management of patients with cancer but the development of anthracycline-induced cardiotoxicity (ACT) remains a significant concern for most clinicians. Recently, genetic approach has been used to identify patients at increased risk of ACT. This systematic review assessed the association between genomic markers and ACT. A systematic literature search was performed in Medline, PubMed, Cochrane Central Register of Controlled Studies, CINAHL Plus, AMED, EMBASE and HuGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 63 publications
(224 reference statements)
1
67
0
3
Order By: Relevance
“…Leong et al indicated that several polymorphisms of pharmacogenetics candidates across the anthracyclines biochemistry and cardiomyopathy pathways are potentially a predictor for anthracycline‐induced cardiotoxicity. However, the evidence is limited and further studies are needed to generate robust genetic predictor(s) …”
Section: Strategies For Preventionmentioning
confidence: 99%
“…Leong et al indicated that several polymorphisms of pharmacogenetics candidates across the anthracyclines biochemistry and cardiomyopathy pathways are potentially a predictor for anthracycline‐induced cardiotoxicity. However, the evidence is limited and further studies are needed to generate robust genetic predictor(s) …”
Section: Strategies For Preventionmentioning
confidence: 99%
“…Overall, most candidate gene studies are limited by small patient numbers, lack of replication studies and functional data (66••). A systemic review of 28 candidate gene association studies examined 84 different genes and 147 single nucleotide polymorphisms [67]. Three risk variants in genes ABCC2 , CYBA , and RAC2 significantly increased the risk for anthracycline-induced cardiotoxicity.…”
Section: Studies Of Chemotherapy-induced Cardiotoxicity In Mice and Hmentioning
confidence: 99%
“…The other mechanisms include the formation of toxic drug metabolites, inhibition of nucleotide and protein synthesis, release of vasoactive amines, suppression of specific gene expression, impairment of mitochondrial membrane binding, aggregation of creatine kinase activity, induction of apoptosis, interference of intracellular calcium homeostasis, changes in respiratory chain proteins, induction of nitric oxide synthase, enhancement of mitochondrial cytochrome C release, etc. [11,12]. Other studies have shown that anthracyclines can lead to myocardial cell damage, inducing cardiac mitochondrial diseases and impairment of mitochondrial DNA and the respiratory chain in chronic cardiomyopathy [13][14][15].…”
Section: Discussionmentioning
confidence: 99%